A simple lattice Boltzmann model for turbulence Rayleigh–Bénard thermal convection. (2nd September 2015) - Wei, Yikun; Wang, Zhengdao; Yang, Jianfei; Dou, Hua-Shu; Qian, Yuehong
Highlights: A mesoscopic external force term is added to the LBM equation to consider effect of buoyant body force. The proposed LBM model based on DNS is able to simulate turbulence Rayleigh–Bénard convection. The Nu and Ra are linear in logarithmic scale which accord with DNS and empirical value. The spectra of the velocity and temperature agree well with Bolgiano–Obukhov-like ( BO59 ). Abstract: A simple lattice Boltzmann thermal model is proposed for simulating the turbulence Rayleigh–Bénard convection. This new model introduces a mesoscopic external force term in the lattice Boltzmann equation to consider the effect of the buoyant body force and introduces a temperature density distribution function to simulate the temperature field. The macroscopic density and velocity fields are simulated using the density distribution function. The results show that this simple model is able to simulate turbulence Rayleigh–Bénard convection in the current simulation range of 10 6 ⩽ Ra ⩽ 10 12 . It is shown that the energy spectra of the velocity and temperature are in good agreement with the Bolgiano–Obukhov-like ( BO59 ) scaling.